THE RELATIONSHIP BETWEEN ANXIETY IN PATIENTS WITH DIABETES MELLITUS AND INCREASED BLOOD SUGAR LEVELS IN THE WORKING AREA OF THE TANAH JAVA HEALTH CENTER, SIMALUNGUN DISTRICT, 2020 - Doortua, Doortua; Wooton, Ian; Firdasari, Firdasari; Maswan, Maswan; Wahyuni Tarigan, Sri (International Conference on Health Science, Green Economics, Educational Review and Technology, 2019)
Diabetes mellitus can cause complications that affect all organs in the body. Anxiety is a response to the disease that is felt by the sufferer as pressure, discomfort, anxiety, disappointment because they are tired of the medication regulations that must be carried out resulting in the patient's blood sugar levels not being controlled properly. blood sugar levels in the working area of the Tanah Jawa Community Health Center, Simalungun Regency in 2020.The research design isThis type of research is cross-sectional conducted in August - October 2020. The population and sample in this study were all diabetes mellitus patients in the work areaTanah Jawa Community Health Center, Simalungun Regency, in 2020, namelyas many as 30 people. The results of the study showed that the majority of respondents experienced moderate anxiety, namely as many as 12 people, while a minority experienced severe anxiety, namely as many as 2 people, the majority of respondents experienced increased blood sugar levels, namely as many as 24 people, while the minority did not experience increased blood sugar levels, namely as many as 6 people. From the results of the chi-square test, the cross-table of knowledge and attitudes obtained a p-value of 0.009 <0.05. It can be concluded that anxiety has an influence on increasing blood sugar levels in people with diabetes mellitus in the working area of the Tanah Jawa Health Center, Simalungun Regency, in 2020.This research can provide guidance and motivation for diabetes mellitus clients in controlling blood sugar levels and provide additional information for patients and familiesimplementing prevention and control